Wine Traceability - Cravero, Maria Carla (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Wine traceability is a central theme in the current world market where consumers are increasingly demanding the quality and origin of food and drink. The wine production chain and wine composition are generally controlled by different laws (International Organization of Vine and Wine (OIV), European Union (EU), and national governments) and need specific documentation. Nevertheless, wine production is subject to fraud. Consequently, the improvement of the methods applied to verify the origin and quality of wines is very important to protect wine consumers and producers. In this book, eight different papers—six research papers and two reviews—address the topic from different points of view.